The rise of the food risk society and the changing nature of the technological treadmill - Lioudmila Chatalova; Daniel Müller; Vladislav Valentinov; Alfons Balmann (Sustainability, 2016)
Economic development of transition and developed countries is associated with increasingly unhealthy dietary habits among low-income population segments. Drawing on Ulrich Beck's sociological theory of risk society, the present research note calls attention to the positive relation between national economic development and food risks that result in the rise of food-related diseases and healthcare costs. On this basis, we argue that the knowledge-intensive agribusiness may translate Cochrane's technological treadmill into Beck's risk treadmill that shifts a growing share of food-related healthcare costs from producers toward consumers, state, and the healthcare system. This argument motivates a novel research program dealing with the “food risk treadmill” that emerges in response to modern farming and agribusiness practices. Awareness of the food risk treadmill may help to streamline the development of agricultural science and to prevent it from being excessively dominated by the agricultural and food industry.
Keywords: 330; agricultural treadmill; risk shifting; risk society; Ulrich Beck; knowledge